Attitudes towards persons with intellectual disabilities in adolescents - Wieczorek, Marta; Sadziak, Aleksandra; Matczak, Dawid (Journal of Education, Health and Sport, 2019)
INTRODUCTION An increased interest in the field related to disability results in a change of social approach towards disability. However, the attitudes towards persons with disabilities constantly depend mainly on the type and the degree of disability, including physical, psychosocial disorders or intellectual disabilities. The situation for the latter group seems to be the least favourable, and thus contacts with persons with intellectual disabilities are still limited.AIM OF RESEARCH The aim of the study is to determine what attitudes towards persons with intellectual disabilities are present among adolescents and what changes in these attitudes occur through their participation in educational activities carried out purposely.MATERIALS AND METHODS The research method is a diagnostic survey and a pedagogical experiment - a one group technique. To determine the attitudes of adolescents towards persons with intellectual disabilities the Scale of Attitudes Towards Disabled Persons (PWON) by Sękowski was used. In the pedagogical experiment, the scenarios of lessons based on "Join us” Education Program for Special Olympics Poland were used. A cohort of 47 students aged 15 - 16 years, including 26 girls and 21 boys participated in the study.RESULTS The gender of respondents is not the factor which significantly differentiated attitudes towards persons with disabilities both before and after the pedagogical experiment. The pedagogical experiment changed the attitudes represented by investigated adolescents to more positive ones. CONCLUSIONS "Join Us" Education Program for Special Olympics is an effective tool for stimulating positive attitudes toward persons with intellectual disabilities among adolescents. It seems that the educational process should be supplemented with lessons devoted to the problem of intellectual disability, which will increase the awareness of adolescents and lead to integration of communities with intellectually disabled persons.